Literasi Keuangan Dan Persepsi Risiko Keuangan Terhadap Keputusan Penggunaan SPaylater Dikalangan Mahasiswa - Sahroyani, Mira; Alpiansah, Restu; Dethan, Stevany Hanalyna; Anggriani, Rini; Widiyasti, Baiq Dinna (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
Digital financial services like SPayLater are increasingly popular among students due to their payment flexibility. However, using these services carries financial risks such as high interest rates, late payments, and lowered credit scores. These issues are exacerbated by low levels of financial literacy and risk perception among students, which can influence unwise decisions about using SPayLater.This study aims to determine the influence of financial literacy and perceived financial risk on the decision to use SPayLater. The study was conducted on students at the Faculty of Economics and Business, Bumigora University, using a quantitative approach and purposive sampling technique. The number of respondents in this study was 100 student SPayLater users.Data were collected through questionnaires and analyzed using IBM SPSS version 26 software. The variables used in this study included financial literacy, perceived financial risk, and the decision to use SPayLater. The analysis was conducted using multiple linear regression to determine the partial and simultaneous effects between variables.The results of the study indicate that financial literacy and perceived financial risk have a positive and significant influence on the decision to use SPayLater, both partially and simultaneously. These findings indicate that students with high levels of financial literacy and perceived risk tend to be wiser and more selective in using this service. This research is expected to serve as a reference for educational institutions and financial service providers in improving student financial literacy.